1999
DOI: 10.1161/01.cir.100.7.736
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Markers of Hemostatic Function With Risk of Ischemic Stroke

Abstract: for the Atherosclerosis Risk in Communities (ARIC) Study InvestigatorsBackground-Several markers of hemostatic function and inflammation have been associated with increased risk of coronary heart disease, but prospective evidence for their role in ischemic stroke is scant. Methods and Results-The Atherosclerosis Risk in Communities (ARIC) Study measured several of these markers in more than 14 700 participants 45 to 64 years old who were free of cardiovascular disease and were followed up for 6 to 9 years for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
269
10
9

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 377 publications
(300 citation statements)
references
References 37 publications
12
269
10
9
Order By: Relevance
“…23,34,35 In humans, the antithrombotic factor protein C is protective in ischemic stroke. 36 The present study confirms that a deficiency of tPA favors fibrin deposition in brains challenged by a thrombotic ischemic insult, which in turn enhances ischemic brain injury. These findings provide direct evidence for a causal relationship between reduced fibrinolytic activity and ischemic neuronal damage, suggesting that endogenous tPA promotes desirable thrombolytic and protective effects in cerebral ischemia, and that factors other than tPA must be responsible for ischemic neuronal damage.…”
Section: Discussionsupporting
confidence: 83%
“…23,34,35 In humans, the antithrombotic factor protein C is protective in ischemic stroke. 36 The present study confirms that a deficiency of tPA favors fibrin deposition in brains challenged by a thrombotic ischemic insult, which in turn enhances ischemic brain injury. These findings provide direct evidence for a causal relationship between reduced fibrinolytic activity and ischemic neuronal damage, suggesting that endogenous tPA promotes desirable thrombolytic and protective effects in cerebral ischemia, and that factors other than tPA must be responsible for ischemic neuronal damage.…”
Section: Discussionsupporting
confidence: 83%
“…Accordingly, our findings stand against the notion that the beneficial CV effects of MD) are mediated through by a decrease in platelet reactivity. We also found that plasma vWF, considered a HCVRF (Folsom et al, 1999;Smith et al, 2000), did not change significantly with MD. This result suggests that the CV benefit of MD would not be mediated by a decrease in plasma vWF levels.…”
Section: Discussionmentioning
confidence: 49%
“…25 As well as being a risk factor for coronary artery disease, von Willebrand factor is also a risk factor for stroke, which is a particular concern in hypertensive patients. For example, in the Atherosclerosis Risk in Communities Study, 26 the risk of stroke rose significantly for each standard deviation increase in von Willebrand factor.…”
Section: Discussionmentioning
confidence: 99%